Seleção, avaliação do crescimento e alterações bioquímicas em plantas de beterraba tratadas com leveduras para controle de cercosporiose - Heling, Anderson Luis (2019)
Yeasts are potential agents of biological control of plants diseases and inductors of resistance of plants to pathogens. This work aimed the selection of yeasts with potential to control of cercosporiosis (Cercospora Beticola) in beet plants based on the reduction of severity and action mechanisms. Evaluation of resistance induction provided by the selected yeasts or their exudates presents in yours filtrates culture and to evaluate growth aspects and productivity as a function of the treatments with yeasts and their filtrates. Initially were tested 44 isolated yeasts in greenhouse about your potential of cercosporiosis control. Of these was selected 31, which were tested in vitro about production of volatile composts, wich 19 that were selected and tested about production of non-volatile composts. After these evalution, was selected three yeasts isolate, which live cells and filtered were tested in relation to beet plants development and biochemical changes, when treatments are used to cercosporiais. The variables analyzed for the development of the plants were: number of leaves; dry mass of leaves, petiole, hypocotyl, root, total aerial part; leaf area; production; severity and área runder disease progress curve (AACPD). Regarding the biochemical alterations, the following variables were analyzed: total phenols; lignin; total proteins, peroxidases activity, β-1,3-glucanases and phenylalanine ammonialyase. The yeasts Candida albicans, Pichia pini and JRS Amarela were selected as potentials for the control of cercosporiasis in beet plants. The treatments with the selected yeasts did not present significant fitness cost, not impacting in the development nor in the production of the plants treated with them. Plants treated with selected yeasts cheged lignins, total phenols and total proteins, indicating a possible induction of resistance as a function of the application of the cells and culture filtrates of these yeasts.